Death on the night of lost lizards : a Hungarian tea house mystery - Buckley, Julia, 1964- (Buckley, Julia, 1964- Hungarian tea house mystery., 2021)
After a professor of Hungarian Studies at the local college is brutally murdered, Hana gets one of her visions that pulls her into the investigation and places her in the path of a killer.